A New Cluster-Based Financial Vulnerability Indicator: The Analytical Concept and its Application for Stress Testing in a Post-Socialist Economy - Ivana Herceg; Danijel Nestić (The Vienna Institute for International Economic Studies (wiiw), 2012)
This paper proposes a new approach to household financial vulnerability analysis by employing cluster analysis techniques in the identification of potentially vulnerable households. The cluster-based vulnerability indicator is combined with a binary dependant variable model and used in stress testing. The proposed methodology is applied to householdlevel data for a post-socialist economy – that of Croatia – with the specific aim of testing the extent to which the prolonged economic downturn following the Great Recession of 2008-2009 might hurt indebted households. The paper compares the results based on the new approach with those based on traditional stress testing methods. Interest rate shocks had a stronger impact on household vulnerability in the traditional approach, whereas decreases in employment are found to be more disruptive in the cluster-based approach.
Keywords: 330; household financial vulnerability; cluster analysis; stress testing; Croatia